Aptamer-recognized carbohydrates on the cell membrane revealed by super-resolution microscopy. Issue 16 (11th April 2018) - Jing, Yingying; Cai, Mingjun; Xu, Haijiao; Zhou, Lulu; Yan, Qiuyan; Gao, Jing; Wang, Hongda
Abstract : By using dSTORM, aptamer-recognized method was compared with lectin-recognized method on visualizing the detailed structure of GalNAc at the nanometer scale. Abstract : Carbohydrates are one of the most important components on the cell membrane, which participate in various physiological activities, and their aberrant expression is a consequence of pathological changes. In previous studies, carbohydrate analysis basically relied on lectins. However, discrimination between lectins still exists due to their multivalent character. Furthermore, the structures obtained by carbohydrate-lectin crosslinking confuse our direct observation to some extent. Fortunately, the emergence of aptamers, which are smaller and more flexible, has provided us an unprecedented choice. Herein, an aptamer recognition method with high precise localization was developed for imaging membrane-bound N -acetylgalactosamine (GalNAc). By using direct stochastic optical reconstruction microscopy (dSTORM), we compared this aptamer recognition method with the lectin recognition method for visualizing the detailed structure of GalNAc at the nanometer scale. The results indicated that GalNAc forms irregular clusters on the cell membrane with a resolution of 23 ± 7 nm by aptamer recognition. Additionally, when treated with N -acetylgalactosidase, the aptamer-recognized GalNAc shows a more significant decrease in cluster size and localization density, thus verifying better specificity of aptamers than lectins. Collectively, our study suggests that aptamers can act as perfect substitutes for lectins in carbohydrate labeling, which will be of great potential value in the field of super-resolution fluorescence imaging.